2021
DOI: 10.1007/s10120-021-01197-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific prognostic effect of CD66b-positive tumor-infiltrating neutrophils (TANs) in gastric and esophageal adenocarcinoma

Abstract: Background Tumor-associated neutrophils (TANs) have recently been identified as a relevant component of the tumor microenvironment (TME) in solid tumors. Within the TME TANs mediate either tumor-promoting or tumor-inhibiting activities. So far, their prognostic relevance remains to be determined. This study aims to evaluate the prognostic relevance of TANs in different molecular subtypes of gastric and esophageal adenocarcinoma. Methods We analyzed a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Female gastric cancer patients had a better prognosis, and this fnding was consistent with most previous studies [9][10][11][12][13][14][15][16][17][18]. Tere are many possible reasons for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Female gastric cancer patients had a better prognosis, and this fnding was consistent with most previous studies [9][10][11][12][13][14][15][16][17][18]. Tere are many possible reasons for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
“…Studies on the prognosis of gastric cancer in females have produced mixed results. While in most studies, female patients had a better prognosis [9][10][11][12][13][14][15][16][17][18], several other studies showed no independent sex-related associations with OS [19][20][21][22]. Tough some recent studies have found that females had a better overall prognosis, this was not found to be the case in young female patients [23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…In a European gastric cancer cohort study, immunohistochemical staining of myeloperoxidase was used to show a correlation between TAN density and survival in women but not in men. These findings indicate a possible sex-specific prognostic effect of TANs ( 116 , 117 ). In two independent clinical cohorts, the ratio of CD8 + T cells to TANs within the tumor was associated with anti-PD1 monotherapy failure in non-small cell lung cancer (NSCLC) patients, indicating that neutrophil antagonism may be a sustainable secondary therapeutic approach to boost ICI treatment outcomes ( 118 ).…”
Section: Neutrophils: Cells With a Multitude Of Rolesmentioning
confidence: 63%
“…With more men than women being affected by GEA (6.6 [8.2]/1.8 [3.8], region-specific incidence for age-standardized rates by sex for esophageal cancer [stomach] in 2020, Western Europe [15]), one should also appreciate that sex may be considered as a variable in future trials and clinical management of GEA patients (Figure 1) [76][77][78][79][80]. Given the relevance of sex differences in cancer mortality, molecular and genetically, as well as pharmaceutically, future studies need to define the underlying mechanisms for these differences when studying the TME of GEA [81].…”
Section: The Tme Of Geamentioning
confidence: 99%